2011
DOI: 10.1080/01932691003659270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium on the Phase Distribution of Resin and Fatty Acids in Pitch Emulsions

Abstract: Resin and fatty acids (RFAs) play a key role in deinking processes of recycled fiber after precipitation by calcium. The distribution of RFAs between the lipophilic/colloidal phase and the water phase, here called pK lw , was determined by gas chromatography for different emulsions of TMP pitch and fatty acid soaps in the presence of calcium ions. Resin acids were at least partially dissolved at alkaline conditions even at high calcium ion concentrations, while fatty acids were only slightly soluble. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The dominating components in the eucalyptus and birch kraft pulp were fatty acids and sterols, as expected (Ekman and Holmbom 2000). It is known that the water-solubilities of long-chained fatty acids are very limited even at alkaline pH, and can be severely decreased at high conductivity values (Sundberg et al 2009;MacNeil et al 2011). This fact makes it very difficult to completely remove fatty acids by alkaline washing, even after kraft pulping.…”
Section: Resultsmentioning
confidence: 99%
“…The dominating components in the eucalyptus and birch kraft pulp were fatty acids and sterols, as expected (Ekman and Holmbom 2000). It is known that the water-solubilities of long-chained fatty acids are very limited even at alkaline pH, and can be severely decreased at high conductivity values (Sundberg et al 2009;MacNeil et al 2011). This fact makes it very difficult to completely remove fatty acids by alkaline washing, even after kraft pulping.…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding studies with addition of calcium chloride showed that calcium ions lower the solubility even more dramatically, especially for saturated acids and oleic acid [25]. Resin acids were less affected by the addition of calcium, and dehydroabietic acid was only a little influenced, even by addition of 10 mM of calcium ions.…”
Section: Resin and Fatty Acids As Surfactantsmentioning
confidence: 88%
“…Resin acids and terpenes, which often comprise about 0.6 to 0.9% of the dry mass of conifers used for pulping (Fengel and Wegener 1984), are often the major component in pitch-like deposits on papermaking equipment and related spots on the paper product (Back 2000;McLean et al 2005b;McLean 2008;Strand 2013). As noted by Back (2000) and MacNeil et al (2011), the resin acids are generally more water-soluble but more viscous than the fatty acids. Triglyceride esters of fatty acids are especially prominent in fresh wood chips and in wood harvested in the wintertime in temperate climates (Blazey et al 2002).…”
Section: Pitch-related Problems In Pulp and Paper Millsmentioning
confidence: 91%
“…This is consistent with deprotonation of fatty acids or other species due to stabilization of the ionic forms as a result of shielding effects. Örså et al 1997;MacNeil et al 2011…”
Section: Salt Concentrationmentioning
confidence: 99%